Konsiderasi Teknik Anestesi pada Crash Ponek Fetal Distress - Apsari, Ratih Kumala Fajar; Uyun, Yusmein; Adrin, Olga Elenska (Jurnal Komplikasi Anestesi, 2021)
Neonatal and infants’ mortality rate in Indonesia is still high. Emergency case in comprehensive obstetric and neonatal emergency care is one of the causes related to high mortality rate in pregnancy and neonates. There is a thin line between true emergency which may need emergency surgery, previously known as crash-C-section and emergency that could be optimized before surgery is performed. A true emergency may need considerable anesthesia technique which could be done quickly yet also emphasizes on patient’s safety.